Symmetric and asymmetric overgrowth of a Ag shell onto gold nanorods assisted by Pt pre-deposition. Issue 55 (25th October 2021) - Zhang, Qi; Deng, Tian-Song; Wei, Ming-Zhang; Chen, Xi; Cheng, Zhiqun; Li, Shiqi; Gu, Yi-Jie
Abstract : Demonstrating asymmetric (AuNR–Pt)–Ag tri-metallic nanostructures by a two-step seed-mediated method. The shell thickness was controlled by the amount of AgNO3 . Abstract : The plasmonic properties of noble metallic nanoparticles could be tuned by morphology and composition, enabling opportunities for applications in sensors, photocatalysis, biomedicine, and energy conversion. Here, we report a method of the symmetric and asymmetric overgrowth of a Ag shell onto gold nanorods assisted by Pt pre-deposition via a 2-step approach. Firstly, gold nanorods (AuNRs), synthesized via a seed-mediated method, were used as seeds to form a AuNR–Pt structure, by using K2 PtCl4 as the precursor. In this step, most of the Pt material was selectively deposited on the tips of the AuNR. Secondly, by using AgNO3 as the precursor, a Ag shell was overgrown on the surface of the AuNRs–Pt nanoparticles, resulting in a (AuNR–Pt)–Ag core–shell tri-metallic nanostructure. Due to the surface energy and lattice matching between Au and Ag, the Ag shell preferred to be epitaxially overgrown on the side of AuNR. The Ag shell thickness and symmetry of the (AuNR–Pt)–Ag could be tuned by changing the amounts of AgNO3 precursor. With the increase of the Ag shell thickness, the (AuNR–Pt)–Ag nanostructures changed from symmetric to asymmetric. The obtained (AuNR–Pt)–Ag nanostructures were studied using UV-vis-NIR spectroscopy, transmission electron microscopy, EDS mapping, DLS, and ICP-MS. The growth mechanism was discussed.